Anthropometric characteristic and body composition of female students involved in volleyball training - Kutseryb, T.; Hrynkiv, M.; Vovkanych, L.; Muzyka, F.; Melnyk, V. (Anthropological Review, 2023)
There have been only few studies investigating the anthropometric characteristics of female volleyball players. These studies have revealed a positive influence of volleyball training on the physical development and fitness level among girls and women. The aim of the study was to assess the anthropometric profile of young female volleyball players. Our sample consisted of twelve female volleyball players aged between 18-21 years with at least 5 years of training experience. The body height and mass, the thickness of skinfolds, longitudinal dimensions of the body, girth and breadths were measured. The body composition was determined using anthropometric and bioimpedance methods. Somatotype was determined according to the calculating method of J. E. L. Carter. The body height of the volleyball players was estimated as high, and the body mass - higher than average. Middle shoulders, narrow pelvis and prevailing of longitudinal dimensions were the most distinctive features of the body proportions of the female volleyball players. Although their thorax was narrow, the respiratory muscles were well developed. The male type of proportions was typical for players exhibiting a theinoid scheme (middle shoulders, long legs) according to V.V. Bunak. Our data showed high development of the muscular component of the body of volleyball players, comparable to females professionally involved in sport . Index of muscle development, based on the excursion of the shoulder muscles, was typical for female athletes - 9,92 ± 2,98 cm. We also found that the relative mass of the fat component was within the normal range for elite volleyball players. The central somatotype was found to be typical for the female volleyball players: endomorphy - 3,98 ± 0,58, mesomorphy - 3,38 ± 1,01, and ectomorphy - 3,67 ± 0,76. The obtained results describe the morphological profile of female volleyball players and can be used for the monitoring of their fitness level.